Effect of weathered on the pore characteristics of different rocks in coal-bearing strata - Dong Feng; Enke Hou; Xiaoshen Xie; Pengfei Hou; Jiangbo Wei (PLoS ONE, 2025)
This study aims to explore how weathered controls the microscopic pore development of rocks. Siltstones to coarse sandstones were selected from the main rocks of the Jurassic strata of the northern Ordos Basin. The pore structure, mineral composition, the pore size distribution (PSD), porosity, permeability and fractal characteristics of unweathered and weathered rocks were analysed using a combination of X-ray diffraction (XRD), scanning electron microscopy (SEM) and low-field nuclear magnetic resonance (LF-NMR). The study showed that the microstructure of different sandstones has obvious differences, the total porosity and permeability of rocks are usually positively correlated with the grain size of the rock, and the microscopic pore structure of rocks of the same lithology changes from small pore type to large pore type after weathered. The results show that weathered rocks had the same mineral composition as unweathered rocks specimens but different intensity peaks. It can be clearly seen that the intensity of clay minerals significantly increased in the weathered rock. whereas the proportion of quartz and feldspar decreases correspondingly. The proportion of clay minerals present in the sandstone increases from 4.75% to 13.25% as a consequence of weathered. The sandstone, which exhibited a greater proportion of micropores and fine pores prior to weathered, demonstrated a higher prevalence of macropores and a corresponding increase in fractal dimensions following weathered. The fractal dimensions D1, D2, and DT of the various lithologies exhibited an overall decreasing trend with an increase in particle size. It should be noted that a rock with the same fractal dimension or porosity may exhibit different microporous structures. The research results play an important theoretical support for the prediction of the degree of water enrichment when encountering the weathered sandstone in the process of coal mining, and have an important theoretical significance for the prevention of water hazards that may be encountered in the process of coal mining.